Obstetric profile and complications of puerperas assisted in home visits - Jéssica Medeiros Minasi; Alessandra Mendes de Barros; Catharine Silva de Souza; Taimara Martins Pinheiro; Fabiane Ferreira Francioni; Nalú Pereira da Costa Kerber (Rev Rene)
Descriptive exploratory study with quantitative approach that aimed to trace the obstetric profile and identify the major problems/complications faced by women assisted by the Extension Project “Home Visit in Immediate Postpartum”, of the School of Nursing, Universidade Federal do Rio Grande. Semi-structured interviews were conducted with 72 puerperas, and data collected was submitted to descriptive analysis. The women were aged between 14 and 44 years, 41.6% were primigravidas, 34.7% had undergone at least one cesarean section and 13.8% reported one or more abortions. As for complications during pregnancy, anemia and hypertension were the most common; in delivery and postpartum, most reported no complications. Home visit is important to clarify doubts, detect possible abnormalities, conduct orientations, and assist in mother-baby bond.